Karakteristik Ibu dan Pola Asuh Praktek Pemberian Makan Pada Anak Usia Bawah Dua Tahun - Fausiah Nurlan; Nur Atika; Wiwik Ulfia (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
The purpose of this study was to determine the relationship between the characteristics of respondents to the practice of feeding under two years old children in the work area of Puskesmas Binamu Kec. Binamu, Kab. Jeneponto. This research is a cross-sectional study with simple random sampling technique. The sample was mothers who have children under the age of two years, totaling 136 mothers. Data was collected through direct interviews with respondents. Hypothesis testing is done using the Chi Square statistical test, with α 0.05 and coefficient φ (phi). The results of the study are known to the characteristics of maternal education (p = 0.030) and family income (p = 0.002) associated with feeding practices in children under the age of two years. Meanwhile there was no correlation between maternal work (p = 0.514) and the number of family members (p = 0.692) to the practice of providing food for under-two-year-old children. It is recommended to increase counseling about correct feeding practices for children, especially on the amount and frequency of food provided, besides that nutritional information is provided not only to mothers but also to people around mothers.